Emerging competition and risk-taking incentives at Fannie Mae and Freddie Mac - W. Scott Frame; Lawrence J. White (Federal Reserve Bank of Atlanta, 2004)
This paper examines two major forces that may soon increase competition in the U.S. secondary conforming mortgage market: (1) the expansion of Federal Home Loan Bank mortgage purchase programs and (2) the adoption of revised risk-based capital requirements for large U.S. banks (Basel II). The authors argue that this competition is likely to reduce the growth and relative importance of Fannie Mae and Freddie Mac and hence their franchise values and effective capital. Such developments could, in turn, lead to more risky behaviors by these two GSEs. It is this last consequence that warrants greater regulatory awareness.
Keywords: 330